Development of nutty coffee-choco flavored spread. - Suaboksan, Camille Leigh Tacuban (2014.)
The study focused on the development and characterization of the nutty coffee-choco-flavored spread. Three different spread formulations with varying amounts of brewed coffee and cocoa powder, 50:50 (F1), 70:30 (F2), and 90:10 (F3), were prepared. The rest of the ingredients were held the same for three formulations. ANOVA at α = 0.05 was used to compare the Radical Scavenging Activity of the three formulations. No significant difference in the radical scavenging activity of the three formulations was indicated. Kruskal-Wallis Test (α = 0.05) was used to determine if the sensory characteristics (color, flavor, mouthfeel, and spreadability) of the three formulations vary. Only the flavor was not affected by the different ratios of brewed coffee and cocoa powder, while differed significantly, in color, mouthfeel spreadability of the three formulations. The three formulations were subjected to both Preference and General Acceptability (7-point scale) tests to determine the Most Preferred Formulation (MPF). Kramer?s Rank Sum Test (α = 0.05) revealed that no significant differences in the ranking preference among the three formulations. Also, the general acceptability rating indicated no significant difference with each other based on Kruskal-Wallis Test (α = 0.05). However, based on the consistent lowest sum of rank and general acceptability, like very much, of Formulation 2 (F2), it was considered as the MPF. Formulation 2 was described as like very much and had the lowest sum of rank. The MPF was evaluated to have a brown color, with a slightly coarse mouthfeel and slight coffee flavor. The spreadability of the MPF was measured and fell between the two anchor, extremely poor spreadability and ideal spreadability. The MPF spread had a mean pH of 6.90. It had a moisture content of 17.37%, crude fat, 37.63%, crude protein, 9.71%, crude ash, 1.83%, crude fiber, 1.46%, and 32.01% carbohydrates. The spread was considered as a rich source of carbohydrates and fat. The nutty cofee-choco-flavored spread was developed and has high acceptability rating however, it was high in fat.
Thesis (Undergraduate. Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas. 2014
Keywords: Spread; Coffee; Cacao; Cashew